Risk Factors of Candida parapsilosis Catheter-Related Bloodstream Infection - Yamin, Dina Hussein; Husin, Azlan; Harun, Azian (Frontiers in Public Health, 2021)
Catheter-related bloodstream infection (CRBSI) is an important healthcare associated infection caused by various nosocomial pathogens. Candida parapsilosis has emerged as a crucial causative agent for CRBSI in the last two decades. Many factors have been associated with the development of CRBSI including demography, prematurity, comorbidities (diabetes mellitus, hypertension, heart diseases, neuropathy, respiratory diseases, renal dysfunction, hematological and solid organ malignancies and intestinal dysfunction), intensive care unit (ICU) admission, mechanical ventilation (MV), total parenteral nutrition (TPN), prior antibiotic and/or antifungal therapy, neutropenia, prior surgery, immunosuppressant, and type, site, number and duration of catheters. This study aims to determine C. parapsilosis CRBSI risk factors. A retrospective study has been performed in an 853-bedded tertiary-care hospital in north-eastern Malaysia. All in-patients with C. parapsilosis positive blood cultures from January 2006 to December 2018 were included, and their medical records were reviewed using standardized checklist. Out of 208 candidemia episodes, 177 has at least one catheter during admission, 31 cases have not been catheterized and were excluded. Among the 177 cases, 30 CRBSI cases were compared to 147 non-CRBSI (81 bloodstream infections (BSIs), 66 catheter colonizers). The significance of different risk factors was calculated using multivariate analysis. Multivariate analysis of potentially risk factors shows that ICU admission was significantly associated with non-CRBSI than CRBSI (OR, 0.242; 95% CI (0.080-0.734); p=0.012), and TPN was significantly positively associated with CRBSI than non-CRBSI (OR, 3.079; 95%CI (1.125-8.429); p=0.029), while other risk factors were not significantly associated. Patients admitted in ICU were less likely to develop C. parapsilosis CRBSI while patients receiving TPN is more likely to have C. parapsilosis CRBSI when compared to non-CRBSI group.